Bach Perspectives 11 : J. S. Bach and His Sons - Oleskiewicz, Mary (Book collections on Project MUSE., 2017)
Among his numerous children, Johann Sebastian Bach sired five musically gifted sons. The eleventh volume of Bach Perspectives presents essays that explore these men's lives and careers via distinctive and, in several cases, alternative and interdisciplinary methodologies. Robert L. Marshall traces how each of the sons grappled with--and at times suffocated beneath--their illustrious father's legacy. Mary Oleskiewicz's essay investigates the Bach family's connections to historical keyboard instruments and musical venues at the Prussian court, while David Schulenberg looks at Carl Philipp Emanuel Bach's diverse and innovative keyboard works. Evan Cortens digs into everything from performance materials to pay stubs to offer a detailed view of the business of Carl Philipp Emanuel Bach's liturgical music. Finally, Christine Blanken discusses how the rediscovery of Bach family musical manuscripts in the Breitkopf archive opens up new perspectives on familiar topics. A supplemental companion website is now available for Bach Perspectives 11. This resource features additional images, captions, and short descriptions to provide an essential supplement to the printed text [Publisher description].